THE ANALYSIS OF STRATEGIES AND SUPPORTING SYSTEMS IN IMPROVING THE EFFECTIVENESS OF WITNESS AND VICTIM PROTECTION IN LPSK - Yuke Novfitria Hendri; Diyah Ayu Marliyawati; Indira Octavia (MANTRA (Jurnal Manajemen Strategis), 2025)
The Witness and Victim Protection Agency (LPSK) of Indonesia represents a critical institutionalframework for safeguarding vulnerable individuals within the legal system. This comprehensive research investigates the multifaceted strategies and support systems essential for enhancing witness and victim protection effectiveness through a rigorous qualitative methodology.Employing mixed research methods including in-depth interviews with legal professionals, structured observations, extensive documentary analysis, and comparative case studies, the research systematically examines existing protection mechanisms. The study explores complex challenges confronting witness and victim protection, including psychological vulnerabilities, potential retaliation risks, and institutional limitations.Key research findings reveal four pivotal dimensions for protection effectiveness: (1) Integrated Institutional Coordination – developing robust inter-agency protocols and communication frameworks, (2) Technological Infrastructure – creating advanced digital tracking and management systems for witness data protection, (3) Professional Capacity Building –implementing comprehensive training programs addressing psychological, legal, and security dimensions, and (4) Normative Framework Enhancement – recommending legislative refinements to strengthen legal protections.The research demonstrates that effective witness and victim protection transcends traditional legal paradigms, requiring holistic approaches addressing psychological safety, social reintegration, and continuous risk management. Innovative recommendations include establishing specialized psychosocial support units, developing adaptive risk assessment methodologies, and creating confidential relocation and identity transformation protocols.Theoretical contributions include developing a comprehensive conceptual model of institutional protection mechanisms, while practical implications offer actionable strategies for LPSK and related governmental institutions to revolutionize their approach to witness and victim protection.By integrating legal, psychological, and sociological perspectives, this research provides an unprecedented, nuanced understanding of institutional protection strategies, potentially serving as a transformative blueprint for enhancing human rights protections within Indonesia’s judicial ecosystem.